INNOVATIVE APPROACHES IN DEVELOPING COMMUNICATIVE COMPETENCE - Glushenko, Olga; Korenetskaya, Irina; Kuznetsova, Ekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article deals with the aspect of the language acquisition through the use of socioculturally contextualized educational materials and applying particular strategies and techniques to improve communicative skills of the students. We have defined a motivation-stimulating sociocultural principle, and presented both theoretical and practical items in terms of socioculturally contextualized educational materials based on the mentioned above principle. The social demand for a linguistically competent personality faces the problem of the lack of the proper effective educational methods in the classroom. The aim of the research is to study the theory and practice of developing the communicative competence via the innovative approaches in language education. The article also introduces the concept of multiculturalism and global citizenship, national values and beliefs in language education as innovative principles of education, interest to a human being and to another culture as a life skill, we study the definitions of multiculturalism and the phenomenon of interest to a personality, we, identify various types and components within the complex structure of multiculturalism; describe the ways of applications of the principles of multiculturalism into the classroom. We also suggest a model of developing the communicative competence through innovative approaches (with stages, particular algorithms for a teacher, indicators in students’ behavior).